Why Containment Works : Power, Proliferation, and Preventive War - Thies, Wallace J. (Cornell studies in security affairs, 2020)
"This book argues that the U.S. invasion of Iraq in 2003 was unnecessary. Saddam Hussein's murderous tendencies all but destroyed Iraq's ability to strike the West, especially the U.S"--